WORD OF MOUTH, IKLAN, DAN CITRA PERUSAHAAN TERHADAP KEMINATAN KONSUMEN TRAVEL HAJI DAN UMRAH - Agita Putri Belina; A Efendi (Jurnal Perspektif Bisnis, 2019)
This study aimed to determine the influence variable word of mouth, print media ads and company image on the consumers intention to candidate umrah’s consumers in PT. Arminareka Perdana Bandar Lampung either partially or simultaneously. With quantitative approach, sampling technique systematic on 100 respondents. The analysis’s data were conducted by multiple linear regression, uji t, and uji F. The results, there are significant influence between word of mouth, print media ads, and company image on the consumers intention to candidate consumers. Worship tourism are highly valuable experience for customers, positive branding gives big role on spreading good image of the company through word of mouth, which not able reached by conventional advertising media in influencing customer’s intention on having offering package services.